Discourse strategies and their implications in the relation between speaking and writing - A study of parenthesis in chronicle - De Moura Neves, Maria Helena [UNESP] (My University, 2012)
Based on functional theory, the text discusses the relations between spoken language and written language, defending not only the existence of a sole grammatical system for both, but also the relevance of studies contemplating specificities of use, some of these being more directed toward interaction, and others being more directed toward system. The investigation that aims to prove these premises used the chronicle as examination material, due to its linguistic colloquialism in general and due to the chronicler's personal engagement, which involve linguistic strategies available for the expression of information and for the reader's understanding. The investigation was concentrated on the discourse parenthesis, especially on its connection with the degree of language planning and with the creation of view plans and the establishment of emphasis. It was concluded that the resource of parenthesis both represents linguistic informality (which is more directed toward speaking) and shows the care with preparation and marking of style (which is more directed toward writing), illustrating specificities.
As estratégias discursivas e suas implicações na relação entre oralidade e escrita - Um estudo do parêntese na crônica
Keywords: Chronicle; Discourse strategies; Functionality; Parenthesis; Speaking and writing